INDONESIAN AND ENGLISH CODE MIXING IN DAILY CONVERSATIONS BY MALE AND FEMALE STUDENTS AT MAHAD MUHAMMAD SAMAN ISLAMIC BOARDING SCHOOL - Hijrah Novianda; Sri Minda Murni; Busmin Gurning (LINGUISTIK TERAPAN, 2018)
This research was aimed at comparing the use of code mixing  in relation to the pattern of code mixing used by male and female students at Mahad Muhammad Saman Islamic Boarding School Medan. The data of the study were 10 male students and 10 female students’ utterances which contain Indonesian-English code mixing. The research was conducted by using qualitative descriptive design. The instrument used for this study were questionnaire and interview. The data were analyzed  by Miles and Huberman and Saldana data analysis. (1) The research findings showed in the pattern of insertion, females are more frequent used it than males.  Females are  used it 53% and males used it 38%. In the pattern of alternation, males are more frequent used it than females. Males used it 38% but females used it 21%. In the pattern of congruent lexicalization, females are more frequent used it than males.  Females used it 26% but males used it 24%.male students tend to use noun or verb, while female students tend to use the word lah, kan, ya. Keywords:Pattern of code mixing, insertion, alternation and congruent lexicalization.